Analysis of effectiveness of three forest interventionist techniques and proposal of a new and integrated model of forest restoration - Castelli, Karen Regina [UNESP]; Barreto, Mariana Gregorio [UNESP]; Francesconi, Wendy; Valle, Leandro Dalla [UNESP]; Mondelli, Giulliana; Abilio, Fernanda Maria; Silva, Alexandre Marco da [UNESP] (Taylor & Francis, 2015)
We assessed the efficacy of three different forest intervention techniques, in terms of phytosociological and edaphic responses, that were implemented in 2007. In a farm where trees are planted and managed for cellulose production as well as set aside for environmental conservation, four stands were analysed: three of them were considered degraded and were managed using different intervention techniques (transposition, perch, and abandonment), and a fourth stand comprising pristine vegetation was considered a control (reference). Floristic and phytosociology data were collected in three 10 × 10 m plots established in each stand. Also, a total of 48 soil samples were collected to analyse physical and chemical attributes of the topsoil for the different stands. In terms of biodiversity, all the treatments showed significantly lower values when compared to the reference area. However, the soils in all the treatment and reference stands are similar in terms of physical and chemical attributes. Taking into account the specificities of each restoration technique, we verified that the integrated use of a set of management practices, constituted by the (1) abandonment of the area and (2) following a selective killing of the eucalyptus, is the most suitable and promising model to provide fast and effective restoration in terms of environmental indicators.
Keywords: Environmental indicator; Environmental assessment; Forest ecology; Forest restoration technology; Interventionist practices